First Observation of Lion Roar Emission in Saturn's Magnetosheath. Issue 2 (17th January 2018) - Píša, D.; Sulaiman, A. H.; Santolík, O.; Hospodarsky, G. B.; Kurth, W. S.; Gurnett, D. A.
Abstract: We present an observation of intense emissions in Saturn's magnetosheath as detected by the Cassini spacecraft. The emissions are observed in the dawn sector (magnetic local time ∼06:45) of the magnetosheath over a time period of 11 h before the spacecraft crossed the bow shock and entered the unshocked solar wind. They are found to be narrow‐banded with a peak frequency of about 0.16  f ce, where f ce is the local electron gyrofrequency. Using plane wave propagation analysis, we show that the waves are right hand circularly polarized in the spacecraft frame and propagate at small wave normal angles (<10 ∘ ) with respect to the ambient magnetic field. Electromagnetic waves with the same properties known as "lion roars" have been reported by numerous missions in the terrestrial magnetosheath. Here we show the first evidence such emission outside the terrestrial environment. Our observations suggest that lion roars are a solar‐system‐wide phenomenon and capable of existing in a broad range of parameter space. This also includes 1 order of magnitude difference in frequencies. We anticipate our result to provide new insight into such emissions in a new parameter regime characterized by a higher plasma beta (owing to the substantially higher Mach number bow shock) compared to Earth. Key Points: First observation of intense lion roar emission carried out in Saturn's magnetosheath Emission occurs at frequencies of approximately 0.16  f ce as right‐hand circularly polarized waves in the spacecraft frame Poynting flux directions show that waves are generated at the dawn flank magnetosheath close to the bow shock